UNDERSTANDING MENTAL CONDITIONS IN THE ELDERLY BASED ON RELIGIOUS/SPIRITUAL PERSPECTIVE - Effendy, Khusnul Fathoni (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2025)
Introduction – The elderly who lack a sense of meaning in life and do not live mindfully often experience discomfort that leads to emotional turmoil. This phenomenon highlights the fact that becoming elderly requires both physical and mental preparedness. This search influences one’s mindset and understanding of closeness to God, and it has the potential to enhance one’s spirituality. This paper aimed to examine the mental condition of the elderly through their religious/spiritual aspects – beginning with their search for meaning in life, their independent efforts, and their insight into personal circumstances. Methods – This research was conducted as qualitative research with interpretation in a phenomenological aspect. All participants took part in each session of the interview, which was conducted by the author. All participants’ statements were used as content analysis by Colaizzi’s seven-step analysis. Results – Analysis of the data obtained from the verbatim interview results led to five major themes and 17 sub-themes, which led to the meaning of getting old, self-uncomfortableness, mental condition, the meaning of Allah’s presence, the meaning and need of liqo’. Discuss – The elderly who are mentally prepared for old age, mindful, and who need Allah as the source of life, peace, the beginning, and end of life, will attain a high level of religious/spiritual. That refers to being closer to Allah in of natural way, flowing, and calming need, as if it were a primary need. Conclusion – Elderly individuals with a positive outlook perceive the presence of Allah as the center of life, peace, and the source of both the beginning and end of life. The liqo’ activity helps participants become the best version of themselves and strive to be Muslims with the final designation of husnul khotimah, or a good ending.